Systematic determination of disulfide bond reduction potentials reveals a nonequilibrium redox hierarchy in cyanobacteria - Kenya Tanaka; Akihiko Kondo; Tomohisa Hasunuma (Proceedings of the National Academy of Sciences, 2026)
Disulfide bonds act as reversible switches that regulate cellular function in nearly all organisms. Their behavior is set by the midpoint potential ( E m ), yet E m is known for only a small number of sites, mostly in purified proteins studied away from their natural partners. We developed a mass-spectrometry workflow that measures E m directly from native cell lysates. By equilibrating proteins of the cyanobacterium Synechocystis sp. PCC 6803 in defined redox buffers and reading out the oxidation state of individual cysteines, we obtained 368 E m values across the proteome and validated them against purified proteins. A key example is the regulatory protein CP12: its E m in isolation differs strongly from the value measured in lysate and converges only when its physiological partner, thioredoxin, is included, showing that our approach captures the effective potentials that operate inside cells. Combining E m with absolute measurements of cysteine redox state in light and darkness, we mapped intracellular redox “operating points” for Calvin–Benson–Bassham (CBB) cycle enzymes. Phosphoribulokinase sits near thioredoxin, whereas fructose 1,6-bisphosphatase/sedoheptulose 1,7-bisphosphatase (F/SBPase) and CP12 are maintained at more oxidized, nonequilibrium states. These results reveal a hierarchical redox control network in photosynthetic metabolism and provide a general strategy for measuring context-dependent redox switches in living systems.